The association between air pollution and preterm birth and low birth weight in Guangdong, China - Ying Liu; Jihong Xu; Dian Chen; Pei Sun; Xu Ma (BMC, 2019)
Abstract Background A mountain of evidence has shown that people's physical and mental health can be affected by various air pollutions. Poor pregnancy outcomes are associated with exposure to air pollution. Therefore, this study aims to investigate the association between air pollutions (PM2.5, PM10, SO2, NO2, CO, and O3) and preterm birth/low birth weight in Guangdong province, China. Method All maternal data and birth data from January 1, 2014 to December 31, 2015 were selected from a National Free Pre-pregnancy Check-ups system, and the daily air quality data of Guangdong Province was collected from China National Environmental Monitoring Center. 1784 women with either preterm birth information (n = 687) or low birth weight information (n = 1097) were used as experimental group. Control group included 1766 women with healthy birth information. Logistic regression models were employed to evaluate the effects of air pollutants on the risk of preterm birth and low birth weight. Results The pollution levels of PM2.5, PM10, SO2, NO2, CO, and O3 in Guangdong province were all lower than the national air pollution concentrations. The concentrations of PM2.5, PM10, SO2, NO2 and CO had obvious seasonal trends with the highest in winter and the lowest in summer. O3 concentrations in September (65.72 μg/m3) and October (84.18 μg/m3) were relatively higher. After controlling for the impact of confounding factors, the increases in the risk of preterm birth were associated with each 10 μg/m3 increase in PM2.5 (OR 1.043, 95% CI 1.01-1.09) and PM10 (OR 1.039, 95% CI 1.01~1.14) during the first trimester and in PM2.5 (OR 1.038, 95% CI 1.01~1.12), PM10 (OR 1.024, 95% CI 1.02~1.09), SO2 (OR 1.081, 95% CI 1.01~1.29), and O3 (OR 1.016, 95% CI 1.004~1.35) during the third trimester. The increase in the risk of low birth weight was associated with PM2.5, PM10, NO2, and O3 in the first month and the last month. Conclusion This study provides further evidence for the relationships between air pollutions and preterm birth/low birth weight. Pregnant women are recommended to reduce or avoid exposure to air pollutions during pregnancy, especially in the early and late stages of pregnancy.